Beyond Performance : The Mediating Role of Motivation In The Nexus of Leadership, Culture, And Teacher Welfare - Muhammad Deny; Sinta Gisthi Ardhiani; Indana Zulfa Sari; Firda Dwi Rahmawati (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
Teacher performance quality remains a strategic issue in elementary education, particularly in regions with large and diverse teacher populations such as West Java. This study examines the influence of transformational leadership, organizational culture, and teacher welfare on teacher performance quality, with work motivation as a mediating variable. A quantitative explanatory approach was employed using a cross-sectional survey design. The respondents were public elementary school teachers in West Java Province, selected through proportionate stratified cluster random sampling across several regional clusters. Data were analyzed using Structural Equation Modeling with AMOS. The findings indicate that teacher welfare plays the most important role in improving both work motivation and teacher performance quality. Work motivation also mediates the relationship between teacher welfare and teacher performance quality, showing that welfare improvement can strengthen teacher performance by enhancing motivation. In contrast, transformational leadership does not show a significant influence on either work motivation or teacher performance quality. Organizational culture has a negative effect on work motivation, suggesting that a demanding school culture without adequate support may reduce teachers’ intrinsic motivation. These findings highlight that improving teacher welfare, strengthening psychosocial recognition, ensuring workload fairness, and creating a supportive school culture are essential strategies for improving teacher performance quality. This study contributes to educational management literature by emphasizing teacher welfare and work motivation as central mechanisms in strengthening elementary school teacher performance